Improving Students’ Vocabulary Mastery by Kids’ Animation Movie - Ratri Mindarti; Rudha Widagsa (JEdu: Journal of English Education, 2022)
The low ability to master vocabulary can be caused by many things. Ignorance of these factors can cause teachers to be confused to determine the right method in teaching English vocabulary. This study aims to determine the effectiveness of animation movie in students' vocabulary mastery. The population of this study was grade 8 of a Junior High School in Yogyakarta with a sampling of 34 students in class 8F. The data were obtained from vocabulary knowledge in the pre-test and post-test. The total items of pretest and posttest were 40 items for each. After giving the pretest and posttest, then the researchers analyzed the data. The research findings showed that the students of grade 8F had fewer scores in the pretest. After being given treatment, vocabulary mastery was improved. The mean score of the students was 70.00 on the pretest and became 85.44 on the post-test. Therefore, it can be concluded that the use of kids’ animation movie effectively improved students’ vocabulary mastery.